PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI IPA 2 SMA NEGERI 1 PEKANBARU - Latifah, Titin Latifah; Solfitri, Titi Solfitri; ', Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstarct: This research is a class action research with the objective to fix the learning process and to improve student’s math achievements by applying Think Pair Square (TPS) Cooperative Structural Learning Approach Model. The subject of this research are the students of class XI IPA 2 SMA Negeri 1 Pekanbaru at the second semester of academic years 2013/2014, which amounted to 32 students, consists of 16 male and female students with heterogeneous level of academic capabilities. This research consists of 2 cycles, of which each cycle in composed of 4 stages, which is planning, implementation, observation and reflection. In every end of a cycle, daily exams will be implemented. Data collection is done by observation and tests are daily exams. Data analysis is done by narrative descriptive and statistic descriptive analysis. The result from the observation page shows that teacher-student activities had performed well after action has been made. Most of the students have participated actively in the learning process that has been exercised, such as step-by-step learning, presenting student worksheets or question papers, responding a fellow classmate’s presentation, and giving learning conclusions. Students even try to resolve questions that the teacher has given correctly by the end of the learning process. An action is deemed successful when the number of students that reached the Minimum Mastery Criteria had increased by the first and second daily exams. The number of students that reached Minimum Mastery Criteria from the base score, the first and the second daily exams, in that order are 31.3%, 46.9%, and 62.5%. The result of this research shows that the Think Pair Square Cooperative Learning Approach is capable of fixing the learning process and increasing math achievements from the students of class XI IPA 2 SMA Negeri 1 Pekanbaru at the second semester of academic years 2013/2014. Key words: Mathematics learning achievement, Cooperative learning, Think Pair Square, Class action research